KONDISI TERUMBU KARANG DI PERAIRAN PANTAI MALALAYANG KOTA MANADO PROVINSI SULAWESI UTARA - Dannie R.S Oroh; Tommy M. Kontu; Oktavianus Lintong (Sam Ratulangi University, 2022)
Coral Reef data collection activities were carried out at Barracuda Station for the position and coordinates of the location of coral reef data collection. Field data collection activities were carried out on 29 June 2022. Data collection for the assessment of coral reef conditions was carried out using the Underwater Photo Transect (UPT) method. The UPT method is a method that utilizes technological developments, both digital camera technology and computer software technology. Data collection in the field is in the form of underwater photos which are taken by shooting using a Canon 16 underwater digital camera equipped with a compatible underwater housing. The photos from the shooting were then analyzed using CPCe computer software to obtain quantitative data. Barracuda Station is located in Malalayang Village. When the observations were made the weather was very good, not windy and not bumpy. The water conditions are very good with a visibility of approximately 20 meters and no current. Data collection was carried out at a depth of 4 meters on the reef flat. The bottom of the waters consists of dead coral with algae, live coral, and rubble. In general, the percentage of live coral cover observed at Barracuda station was 13.53% which puts the condition of coral reefs at Barracuda station in the